The Origins of Intergroup Resource Inequality Influence Children’s Decision to Perpetuate or Rectify Inequality - An, Jing; Yu, Jing; Zhu, Liqi (Frontiers in Psychology, 2020)
Previous studies have explored children's intergroup resource allocation in the context of preexisting intergroup resource inequality. However, resource inequality between social groups often originates from different factors. This study explored the role of the origins of resource inequality on children's intergroup resource allocations. In Experiment 1, when there was no explicit origin of the intergroup inequality, children of different ages mainly allocated resources in an equal way and 5- to 6-year-olds showed ingroup bias. In Experiment 2, we examined the influence of different origins of intergroup inequality, and found that 5- to 6-year-olds perpetuated intergroup inequality when resource inequality was based on either a structural (regional disparity) or an internal factor (difference in performance). However, 10- to 11-year-olds rectified inequality or allocated equally when intergroup inequality was based on regional disparity, and perpetuated resource inequality when intergroup inequality was based on performance difference. The origins of inequality appear to play an important role in children's intergroup resource allocations, and older children can distinguish different origins of intergroup inequality in resource allocation.